The Changing Nature of Electioneering Campaigns in the Digital Media Era: What is the Future for Nigeria’s Nascent Democracy - Eucharia, Okwumba (Journal of Advanced Research in Journalism & Mass Communication, 2019)
Advancements in information and communication technologies have seriously impacted on electioneering campaigns globally. This was evidenced when the former United States Presidents, Barack Obama deployed digital media as campaign tools in his 2008 presidential election. In Nigeria, President Goodluck Jonathan also deployed it in his 2011 presidential election. Today, digital media have become prominent communication tools through which politicians and political parties solicit votes from the electorate. The essence of this study was to determine the impact of digital media-powered electioneering campaign messages on people of voting age. A total of 385 voters were surveyed using the questionnaire as the instrument for data collection. It was found that while digital media-powered electioneering campaign messages significantly correlate perception about politicians and political participation, they did not correlate voter decision. The theoretical and practical implications of thee results have been explored. How to cite this article: Eucharia O. The Changing nature of Electioneering Campaigns in the digital Media era: What future for Nigeria’s Nascent Democracy. J Adv Res Jrnl Mass Comm 2019; 6(4): 11-17. DOI: https://doi.org/10.24321/2395.3810.201907